The implementation of DigComp (European Digital Skills Framework) for digital competence assessment and evaluation - Danailova, Irina (Research Papers, 2024)
Digitalisation challenges the need for new digital skills and it is important that both employers and employees have a tool that facilitates adaptability and quick response. The specificity of the European market implies a unified approach and therefore the European Commission initiated and supports the development of the European Framework for Digital Skills (DigComp). The aim of presented scientific study is to describe practical aspects and results of methodology (according to DigComp) for testing of employers` digital skills and to suggest ways that it can be incorporated.